Peran Program Edukasi Keuangan dalam Meningkatkan Literasi dan Kemandirian Finansial Masyarakat Desa Taeno, Kelurahan Rumah Tiga, Kecamatan Teluk Ambon - Andre Sapthu; Desry J Louhenapessy; Lisye Magdalena Liur; Korneles Sangur (Jurnal Kabar Masyarakat, 2024)
The financial education socialization program aims to enhance financial literacy and independence among the community in Taeno Village, Rumah Tiga Sub-District, Teluk Ambon District. In this context, low financial literacy is one of the primary challenges faced by the community, particularly in personal and family financial management. This socialization program is designed to provide basic knowledge about budgeting, saving, and debt management, as well as to introduce accessible formal financial products to the community. The main goal is to equip the community with financial skills that help them achieve independence in daily financial aspects. The program implementation method involves face-to-face counseling sessions at the village hall, interactive workshops, and individual mentoring. This socialization also includes an introduction to digital financial services, such as e-wallets and online banking, designed to expand community access to various financial management options. In each session, participants are encouraged to understand the importance of financial planning, regular saving, and avoiding consumptive debt. Program evaluations are conducted periodically through surveys and group discussions to assess improvements in understanding and changes in financial behavior within the community. The results of the socialization indicate an increased understanding of basic financial management and awareness of the importance of financial literacy among the community. Participants in this program have begun to demonstrate better abilities in budgeting, establishing emergency funds, and selecting formal financial products that suit their needs. Additionally, the program helps reduce community dependence on consumptive loans and encourages them to make better use of beneficial formal financial products.